Symptomatology and Coping Resources Predict Self-Care Behaviors in Middle to Older Age Patients with Heart Failure - Lucinda J. Graven; Joan S. Grant; Glenna Gordon (Nursing Research and Practice, 2015)
Background. Symptoms of heart failure (HF) and coping resources, such as social support and social problem-solving, may influence self-care behaviors. Research regarding the influence of HF symptomatology characteristics and components of social support and social problem-solving on self-care is limited. Objective. To identify predictors of HF self-care behaviors using characteristics of HF symptomatology, components of social support and social problem-solving, and demographic and clinical factors. Methods. Using a cross-sectional, correlational predictive design, a convenience sample (N=201) of outpatients with HF answered self-report surveys. Multiple linear regression with stepwise variable selection was conducted. Results. Six predictors of HF self-care were identified: race, symptom frequency, symptom-related interference with enjoyment of life, New York Heart Association Class HF, rational problem-solving style, and social network (β=34.265, R2=0.19, P=0.001). Conclusions. Assessing the influence of race on self-care behaviors in middle to older age patients with HF is important. Clinical assessment that focuses on symptom frequency, symptom-related interference with enjoyment of life, and HF Class might also impact self-care behaviors in this population. Rational problem-solving skills used and evaluation of the size of and satisfaction with one’s social network may be appropriate when assessing self-care.